Analisis Jaringan Perdagangan Padi dan Beras di Kecamatan Tilatang Kamang Kabupaten Agam Sumatera Barat - Anasfisia, Vinia; , Drs. M. Musiyam, M.T.P; , Drs. Dahroni, M.Si (2015)
The title of this study is Paddy and Rice Trading Network Analysis in Tilatang Kamang, Agam, West Sumatera. The objectives of paddy and rice trading network analysis in Tilatang Kamang, Agam, West Sumatera are to determine the variations of paddy productivity and to determine the patterns of spatial network value chain of rice trading in Tilatang Kamang, Agam, West Sumatera. The methods of this study are using field survey analysis and descriptive quantitative analysis. The field survey analysis was conducted by taking some samples from the population of Tilatang Kamang using a questionnaire as data collection tool. There were 4 parameters use in this study, they are; (1) number of farmers (2) rice area (3) type of irrigations (4) number of rice milling units. The conclusions of this study are; the farmers of Tilatang Kamang selling their crops to the traders and wholesalers. The wholesaler will process the paddy into rice and resell them to the small traders and consumers from inside of the province, such as Tilatang Kamang, Bukittinggi, Padang, Pasaman, and Payakumbuh, meanwhile outside of the province, they sell the crops to Riau, Kepulauan Riau, Jambi, Bengkulu, and South Sumatera.